Level of Job Satisfaction in Doctors - Abida Sultana, Rizwana Riaz, Maqsood Hayat, Syed Arshad Sabir (Journal of Rawalpindi Medical College, 2009)
Background: To assess and compare the level of job satisfaction in different medical specialties and to identify the areas needing improvement. Methods: A cross-sectional descriptive study was conducted among doctors of Rawalpindi Medical College and teaching hospitals (Holy Family Hospital (HFH) Rawalpindi General Hospital (RGH) and District Head Quarters Hospital (DHQ) over a period of 3 months from April-July 2006. A total of 99 doctors, 33 each from the department of Medicine, Surgery and Basic Sciences were included in the study by non-probability purposive sampling. Medical officers and registrars of medical and surgical units in teaching hospitals and demonstrators of basic sciences employed in Rawalpindi Medical College were included. Data was collected by means of self designed structured questionnaire. A standardized tool, Warr-Cook-Wall scale was used to assess the level of job satisfaction in doctors. Results: Of the total 99 study participants, 51.5% doctors of basic sciences and 43.9% of clinical sciences (Medicine and Surgery) were satisfied with their total income. Working environment was satisfactory in the opinion of 73% and 66.6% doctors of basic and clinical sciences respectively. Of the study participants, 78.7% were satisfied with the behaviour of colleagues. Overall 60.6% and 44.4% doctors were satisfied with their working hours and system of promotion respectively. Only 42.4% doctors of clinical sciences were satisfied with their work-load. 64.6% were satisfied with the freedom to choose their method of work. Overall job satisfaction was found to be 61.9%. Conclusion: Majority of the doctors are satisfied with their jobs. However a significant number on the clinical side has reservations regarding income, working hours and system of promotion.